2016
DOI: 10.1073/pnas.1521825113
|View full text |Cite
|
Sign up to set email alerts
|

Collybolide is a novel biased agonist of κ-opioid receptors with potent antipruritic activity

Abstract: Among the opioid receptors, the κ-opioid receptor (κOR) has been gaining considerable attention as a potential therapeutic target for the treatment of complex CNS disorders including depression, visceral pain, and cocaine addiction. With an interest in discovering novel ligands targeting κOR, we searched natural products for unusual scaffolds and identified collybolide (Colly), a nonnitrogenous sesquiterpene from the mushroom Collybia maculata. This compound has a furyl-δ-lactone core similar to that of Salvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(82 citation statements)
references
References 48 publications
1
72
4
1
Order By: Relevance
“…Similarly, protein mutation has been employed to generate SAR data for biased signaling (G protein receptor 183, Daugvilaite et al, 2017;GLP-1, Wootten et al, 2016). Chemical scaffolds yielding biased molecules range from modification of natural endogenous agonists to natural products (Gupta et al, 2016). In general, there has been a steady increase in the number of studies on the structural features of molecules required for biased signaling (Tan et al, 2018; and see Table 5).…”
Section: H Biased Signaling In Screening and Lead Optimizationmentioning
confidence: 99%
“…Similarly, protein mutation has been employed to generate SAR data for biased signaling (G protein receptor 183, Daugvilaite et al, 2017;GLP-1, Wootten et al, 2016). Chemical scaffolds yielding biased molecules range from modification of natural endogenous agonists to natural products (Gupta et al, 2016). In general, there has been a steady increase in the number of studies on the structural features of molecules required for biased signaling (Tan et al, 2018; and see Table 5).…”
Section: H Biased Signaling In Screening and Lead Optimizationmentioning
confidence: 99%
“…Initially extracted from the mushroom Collybia maculata ( Basidomycota ) in 1974 by the group of Dr. Pierre Potier, Collybolide (Colly) is a natural product pertaining to the class of sesquiterpenes [ 80 ]. It was only later in 2016 that a study demonstrated the potential of Colly and its diastereoisomers (9-epi-Colly) in pain attenuation [ 66 ]. Due to its structural similarities with Salvinorin A (a common furyl-δ-lactone motif), this agent was tested on human hMOR, hDOR, and hKOR and was found to be very selective of KOR.…”
Section: Kor Biased Agonismmentioning
confidence: 99%
“…Due to its structural similarities with Salvinorin A (a common furyl-δ-lactone motif), this agent was tested on human hMOR, hDOR, and hKOR and was found to be very selective of KOR. When the authors looked at functional selectivity, they showed that Colly was a very potent agonist in [ 35 S]GTPγS assays (EC 50 ≈ 1 nM) and dose-dependently inhibited adenylyl cyclase activity, but was also potent for ERK1/2 phosphorylation suggesting that it acts as a biased agonist of the hKOR though β-arrestin 2 recruitment with this natural product remains unknown [ 66 ]. The effects were reversed upon treatment with NorBNI showing a KOR-mediated effect.…”
Section: Kor Biased Agonismmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a considerable amount of literature has been accumulated, highlighting the potential of natural products as ligands of G protein-coupled receptors (GPCRs). 4,5 These transmembrane receptors with more than 800 members encoded in the human genome are targeted by approximately 35% of US Food and Drug Administration-approved drugs, thus highlighting their…”
Section: Introductionmentioning
confidence: 99%